STUDI KOMPARATIF PARTISIPASI PETANI PADI SAWAH TERHADAP PELAKSANAAN JURUS KEMAMPUAN KELOMPOK TANI DI KECAMATAN BATANG ASAM KABUPATEN TANJUNG JABUNG - Rendra (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
This study aims to determine the participation of members of the implementation of the ability of the ability of farmers groups in the Beginner class and Advanced classes and to find out whether there is a real difference or not between the participation of paddy farmers in the implementation of ability steps of the Beginner class farmers with Advanced classes in the District Batang Asam, West Tanjung Jabung Regency. In the short term it is expected to be able to know and identify various skills of the farmer group capabilities and the participation of farmers in the farmer group capability steps as a basis for increasing the ability and independence of the farmer groups. The method used is to use a combination of qualitative (descriptive) and quantitative methods. The research data were obtained from observations and interviews (in-depth interviews and structured interviews). The data obtained will be processed statistically using Man Withney analysis. This research will be conducted within a period of six months. This research will be very useful for the government and private parties who are directly involved in conducting agricultural extension activities to farmer groups.